French, Tayler. Phantom of the Arts and Culture Centre in Grand Falls-Windsor. - Jarvis, Dale Gilbert, 1971- (2011)
Recording of a ghost story told by Tayler French, a Grade 8 student at St. Peter's Junior High. Recorded in the Newman Wine Vaults Provincial Historic Site as part of the Young Folklorists Program run by the Heritage Foundation of Newfoundland and Labrador in May, 2011. Tayler writes, "This story takes place in the Arts and Culture Centre in Grand Falls-Windsor. The people who work there claim to hear the voice of a deceased man who had worked there for many years, when they are there by themselves. I heard of this story from my stepdad, and my family used to live in Grand Falls-Windsor."